Agreement between the Open Barbell and Tendo Linear Position Transducers for Monitoring Barbell Velocity during Resistance Exercise - Adam M. Gonzalez; Gerald T. Mangine; Robert W. Spitz; Jamie J. Ghigiarelli; Katie M. Sell (MDPI AG, 2019)
To determine the agreement between the Open Barbell (OB) and Tendo weightlifting analyzer (TWA) for measuring barbell velocity, eleven men (19.4 ± 1.0 y) performed one set of 2−3 repetitions at four sub-maximal percentage loads, [i.e., 30, 50, 70, and 90% one-repetition maximum (1RM)] in the back (BS) and front squat (FS) exercises. During each repetition, peak and mean barbell velocity were recorded by OB and TWA devices, and the average of the 2−3 repetitions was used for analyses. Although the repeated measures analysis of variance revealed significantly (p ≤ 0.005) greater peak and mean velocity scores from OB across all intensities, high intraclass correlation coefficients (ICC2,K = 0.790−0.998), low standard error of measurement (SEM2,K = 0.040−0.119 m·s−1), and coefficients of variation (CV = 2−4%) suggested consistency between devices. Positive (r = 0.491−0.949) Pearson correlations between averages and differences (between devices) in peak velocity, as well as associated Bland-Altman plots, showed greater differences occurred as the velocity increased, particularly at low-moderate intensity loads. OB consistently provides greater barbell velocity scores compared to TWA, and the differences between devices were more apparent as the peak velocity increased with low-to-moderate loads. Strength coaches and athletes may find better agreement between devices if the mean velocity scores are only considered.